The Effectiveness of Reciprocal Teaching Method on Students’ Reading Comprehension in Descriptive Text - Abrori, Alfina; Hifdil Islam , Muhammad; Hamdani, Beny (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2023)
This research aims to investigate whether the students who are taught reading in descriptive text through Reciprocal Teaching Method achieve better in reading ability than those who are taught through Conventional Teaching Method and to explain about the advantages that students will get when using Reciprocal Teaching Method in improving students’ reading comprehension . The design of this study was quasi experimental, control class, pretest-posttest because it was conducted in two classrooms. The subjects of the study are tenth grade high school students consisting of 28 students in MAN 2 Probolinggo. They are divided into two classes, namely control class consists of 14 students and experimental class consists of 14 students. The data analysis used Independent T-Test. Based on the result of the calculation of post-test from experimental and control groups, the alternative hypothesis (Ha) was accepted. The result of the study shows that the use of the Reciprocal Teaching Method can improve the students’ reading ability. The Reciprocal Teaching Method gives the students more advantages in improving reading skills compared to Conventional Teaching Method. It proves the hypothesis of the study that students who are taught reading through the Reciprocal Teaching method achieve better in reading ability than those who are taught through Conventional Teaching Method. With the advantages gained from the Reciprocal Teaching Method, students can easily to understand and improve their reading ability. Based on this result, it can be concluded that the Reciprocal Teaching Method can be used as an alternative method to teach reading, so that the students are able to understand the texts comprehensively. It also makes the students more active in the teaching learning process and can improve their ability as well.